2013
DOI: 10.1159/000354806
|View full text |Cite
|
Sign up to set email alerts
|

Models of Short Bowel Syndrome in Pigs: A Technical Review

Abstract: Background: Short bowel syndrome (SBS) is still a life-threatening disease in both children and adults. Although the therapeutic options are improving, challenges still remain, and to overcome these challenges is a major focus of SBS research today. In order to simulate anatomical and physiological conditions similar to those in humans for research, porcine models of SBS are often used. Various approaches for generating SBS models have been described in the literature. Methods/Results: In this work, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 87 publications
0
7
0
2
Order By: Relevance
“…A technical review of 27 articles reporting porcine SBS models demonstrated great heterogeneity in age, weight, and sex of pigs, as well as percent and location of SBR performed. Experimental numbers were low, and mortality ranged from 6 to 18% where reported (52). One report of 75% SBR in 7-day-old piglets reported 8% mortality rate at 28 days; however, the animals were fed a standard amount of calories per body weight daily and were supplemented with electrolytes, additional costly and workintensive interventions (15).…”
Section: Discussionmentioning
confidence: 99%
“…A technical review of 27 articles reporting porcine SBS models demonstrated great heterogeneity in age, weight, and sex of pigs, as well as percent and location of SBR performed. Experimental numbers were low, and mortality ranged from 6 to 18% where reported (52). One report of 75% SBR in 7-day-old piglets reported 8% mortality rate at 28 days; however, the animals were fed a standard amount of calories per body weight daily and were supplemented with electrolytes, additional costly and workintensive interventions (15).…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive drug tacrolimus has direct vasodilative effects on the porcine SMA, which might also be adressed in further studies is the extrapolation of our findings from a porcine model to the clinical situation. Important species‐related pathophysiological distinctions are possible; however, pigs are morphologically and physiologically similar to humans and represent a well‐characterized large animal model for surgical research on intestinal failure and SBTX . Nevertheless, clinical studies are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The development of these latter models is especially relevant, as they represent the types of SBS seen most in human neonates, with resection of the ileum and/or creation of an end‐jejunostomy, and offer the greatest translational benefit. Interestingly, a recent technical review of piglet models of SBS noted a limitation that current piglet models of SBS were inconsistent, and there was a lack of a standardized model 72 . We believe that differences in neonatal piglet models of SBS relate to the fact that SBS is a heterogeneous disease.…”
Section: Emerging Piglet Models Of Neonatal Sbsmentioning
confidence: 99%